Utilization of Social Media in Islamic Religious Education Learning (Problem Analysis and Solutions) - Khairuddin Hasan (At-Tarbiyat, 2021)
Islamic Religious Education teachers should provide innovative learning to their students. The use of social media in learning is one form of this innovation. From several studies that have been carried out, it was found several problems related to the use of social media in learning, such as the lack of insight of parents in using social media, lack of insight of teachers in understanding the use of social media in learning Islamic Religious Education, and lack of control from parents when children study. using social media. The solution offered is that teachers should provide further socialization to parents about the importance of social media as an effective medium and source of learning. Teachers should further deepen their knowledge about the use of social media. Parents must accompany and direct students in using social media.